2005
DOI: 10.1016/j.ijid.2004.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Coccidioidal pericarditis: a case presentation and review of the literature

Abstract: Coccidioidal pericarditis is a rare disease entity that has a relatively unfavorable prognosis, yet many patients present with diagnostic clues to this disorder. An enhanced understanding of the clinical features of coccidioidal pericarditis may lead to improved outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…In 2003, only one human case was reported. 1 There is a national rabies prophylaxis guideline which is mostly based on World Health Organization and the Advisory Committee on Immunization Practices recommendations. 2 Patients bitten by a suspect animal were treated according to the class of exposure described by the Turkish Republic Ministry of Health Rabies Prophylaxis Guidelines.…”
mentioning
confidence: 99%
“…In 2003, only one human case was reported. 1 There is a national rabies prophylaxis guideline which is mostly based on World Health Organization and the Advisory Committee on Immunization Practices recommendations. 2 Patients bitten by a suspect animal were treated according to the class of exposure described by the Turkish Republic Ministry of Health Rabies Prophylaxis Guidelines.…”
mentioning
confidence: 99%
“…5 Coccidioidomycosis with pericardial involvement is a rare entity, with only 23 cases detailed in the literature (Table). 4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Reports have indicated that over 90% (22/24) of these cases occurred in males. While the elderly are at a higher risk of coccidioidomycosis, it appears coccidioidal pericarditis occurred more often in younger individuals (median age ¼ 32.5 years).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac involvement is uncommon and can affect the pericardium, but endocarditis is extraordinarily rare even with documented fungemia [ 1 6 ]. Our literature review identified 6 case reports and 1 conference abstract of Coccidioides endocarditis that met modified Duke′s criteria for definite or possible endocarditis (Table 1 ) [ 7 11 ]. Other reports lack clinical or histopathological confirmation of endocarditis [ 5 , 8 ].…”
Section: Discussionmentioning
confidence: 99%